Desculpem-nos o transtorno(mental), estamos em reforma(psiquiátrica): um olhar histórico sobre o papel da Psicologia no enfrentamento da lógica manicomial. - FONTENELE, Igor Serafim (2024)
With the Psychiatric Reform, new mental health care devices emerged to replace hospitalization in asylums. In Brazil, the 1990s marked these transformations, however, violations of Human Rights are still observed, signaling a maintenance of the institutional logic in the treatment of mental health. The role of psychologists in Brazilian public health falls within the field of mental health, in psychiatric hospitals, following the medical model of care focused on diagnosis, with a predominance of psychotherapy as a clinical working tool. Some transformations in the care model were possible through the creation of the SUS, enabling the insertion of psychologists within the Basic Health Care Network (ABS) and strengthening work in the field of mental health. This research's main objective is to analyze the transformations that occurred in the mental health care service after the Psychiatric Reform, considering the current challenges for the performance of Psychology in the Psychosocial Care Network. This is an integrative review of the literature, of a documentary nature. To this end, a search was carried out in the SCIELO and BVS databases within the period from 2012 to 2023. The thinking of Michel Foucault, as well as the PRISMA instrument, was used as a theoretical basis and analysis of the results. The results of this research point to significant challenges faced by psychology professionals in the context of current mental health care, from the implementation of community services to training in critical situations and the need for transformations in university education. Due to the scarcity of studies focused on the role of psychologists, this research is expected to contribute to a closer look at this field and stimulate new studies on this topic.